Emergency transvenous temporary pacing during rotational atherectomy - Schwarz, Konstantin; Mascherbauer, Julia; Schmidt, Elisabeth; Zirkler, Martina; Lamm, Gudrun; Vock, Paul; Kwok, Chun Shing; Borovac, Josip Andelo; Mousavi, Roya Anahita; Hoppe, Uta C.; Leibundgut, Gregor; Will, Maximilian (Frontiers in Cardiovascular Medicine, 2023)
Objective: We sought to establish the frequency of bail-out need for emergency TPW insertion in patients undergoing RA that have received no upfront TPW insertion.We performed a single-centre retrospective study of all patients undergoing RA between October 2009 and October 2022. Patient characteristics, procedural variables and inhospital complications were registered.Results: A total of 331 patients who underwent RA procedure were analyzed. No patients underwent prophylactic TPW insertion. The mean age was 73.3±9.1 years, 71.6% (n=237) were male, while nearly half of patients were diabetic (N=47.7%, N=158). The right coronary artery was the most common target for RA (40.8%), followed by left anterior descending (34.1%), left circumflex (14.8%) and left main stem artery (10.3%). 20 (6%) of patients required intraprocedural atropine therapy. Emergency TPW insertion was needed in 1 (0.3%) patient only. 8 (2.4%) patients died, however only 1 (0.3%) was adjudicated as possibly related to RA-induced bradycardia. 5 patients (1.5%) had ventricular fibrillation arrest while 9 (2.7%) required cardiopulmonary resuscitation. 6 (1.8%) procedures were complicated by coronary perforation, 2 (0.6%) were complicated by tamponade while 17 (5.1%) patients experienced vascular access complications.Conclusions: Bail-out transvenous temporary pacing is very rarely required during RA. A standby temporary pacing strategy seems reasonable and may avoid unnecessary TPW complications compared to routine use.